To the Question of the Concept of International Custom - Yu. S. Romashev (Московский журнал международного права, 2022)
INTRODUCTION. International custom still remains one of the main sources of international law. It is an external form of consolidation of customary norms of international law. At the same time, despite the rather wide use of the term "international custom", its general scientifc defnition has not yet been developed in science and practice. Tis defnition, in our opinion, should reﬂect the most important features that characterize this legal phenomenon.MATERIALS AND METHODS. Te empirical base of the study was international treaties and international customs, resolutions of the UN General Assembly, materials of the International Court of Justice and the Court of the Eurasian Economic Union, the International Law Commission, the International Law Association. Te theoretical basis of the article is the works of domestic and foreign scientists in the feld of the law of international customs. Te methodological basis of the study was general scientifc and particular scientifc methods of cognition (dialectical method, methods of analysis and synthesis, deduction and induction, and comparative legal method).RESEARCH RESULTS. Te results of the study made it possible to arrive at a new scientifc defnition of international custom and substantiate the approach to the classifcation of international customs. Under international custom, as a source of international law, it is proposed to understand an unwritten agreement, which is a form of consolidation and existence of customary norms of  international law, reﬂecting the general practice of states, other subjects of international law (for local international custom, the practice of a limited number of states), recognized as a legal norm, regulated by international law and enforced by the subjects of international law, for which international custom is legally binding. International customs are of various varieties and can be classifed on various grounds. At the same time, it should be borne in mind that international custom is based on the usual norms of international law. Teir nature, as a rule, predetermines the varieties of international customs.DISCUSSION AND CONCLUSIONS. It is proposed to put as the basis for the course of reasoning: the belonging of international custom to an unwritten source of international law; the need to separate the use of the term "international custom" and the term "customary rule of international law"; the presence of the conciliatory nature of international custom; taking into account the legal force of international custom in relation to the diﬀerent composition of the subjects of legal relations, the binding nature of international custom for the states associated with its assistance; the impossibility of considering the process of formation of international customs as a source of international law, its further functioning without taking into account the peculiarities of the norms contained in it; the presence of a two-element structure of the norm contained in international custom; taking into account the possibility of regulation by international law of the procedure for the conclusion, operation and termination of an international custom.